Penerapan Media Gambar untuk Meningkatkan Hasil Belajar IPA Kelas IX SMP 8 Kunto Darussalam - Yustini Yustini (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study is purposed to determine the acquisition of students' science learning achievement by using pictures as learning media in classroom IX of SMP Negeri 8 Kunto Darussalam academic year 2018/2019. Data retrieval was carried out on July 2018 until September 2018. The subjects of this study were students of grade IX  at SMP Negeri 8 Kunto Darussalam, with a total number of students was 26 which consisting of 12 men and 14 women. The measured parameters are students learning achievements in the form of absorption and completeness of learning obtained from quizzes in each meeting and block test in each basic competency. Data were analyzed descriptively. Increased student learning achievements can be seen from the absorption and completeness of students' learning before and after the research. Before doing the research, the absorptive capacity of students was 58% with learning completeness 44%, after action research has been done in Cycle 1 the absorption of students was 68% with learning completeness 82.86% and in Cycle 2 the absorption of students was 78% with 100% learning completeness. While the scientific performance of students in the first cycle (72.8%) and cycle II (85.6%). The results of this study indicate that the use of pictures as a learning media in the learning process can improve the students' learning achievements of class IX at SMP Negeri 8 Kunto Darussalam in the academic year 2018/2019.